Isolation of alkaloids from Citrus grandis (Linne) Osbeck (Fam. Rutaceae) - Ellado, Estela R.
The dry powdered rot bark of Citrus grandis was extracted with ethanol by percolation. The extract was partitioned between CHCI3-H2O and the CHCI3 layer was concentrated. TLC were conducted to determine the appropriate eluent for column chromatography. Spraying the spots obtained in TLC with Dragendorff reagent showed that alkaloids were present in the sample. Moisture content and ash content of the material were also determined.